Is Nigeria winning the battle against malaria? Prevalence, risk factors and KAP assessment among Hausa communities in Kano State. (December 2016) - Dawaki, Salwa; Al-Mekhlafi, Hesham; Ithoi, Init; Ibrahim, Jamaiah; Atroosh, Wahib; Abdulsalam, Awatif; Sady, Hany; Elyana, Fatin; Adamu, Ado; Yelwa, Saadatu; Ahmed, Abdulhamid; Al-Areeqi, Mona; et al.
Abstract Background Malaria is one of the most severe global public health problems worldwide, particularly in Africa, where Nigeria has the greatest number of malaria cases. This community-based study was designed to investigate the prevalence and risk factors of malaria and to evaluate the knowledge, attitudes, and practices (KAP) regarding malaria among rural Hausa communities in Kano State, Nigeria. Methods A cross-sectional community-based study was conducted on 551 participants from five local government areas in Kano State. Blood samples were collected and examined for the presence ofPlasmodium species by rapid diagnostic test (RDT), Giemsa-stained thin and thick blood films, and PCR. Moreover, demographic, socioeconomic, and environmental information as well as KAP data were collected using a pre-tested questionnaire. Results A total of 334 (60.6 %) participants were found positive forPlasmodium falciparum . The prevalence differed significantly by age group (p  < 0.01), but not by gender or location. A multivariate analysis showed that malaria was associated significantly with being aged 12 years or older, having a low household family income, not using insecticide treated nets (ITNs), and having no toilets in the house. Overall, 95.6 % of the respondents had prior knowledge about malaria, and 79.7, 87.6 and 95.7 % of them knew about the transmission, symptoms, and prevention of malaria, respectively. The majority (93.4 %) of the respondents considered malaria a serious disease. Although 79.5 % of the respondents had at least one ITN in their household, utilization rate of ITNs was 49.5 %. Significant associations between the respondents' knowledge concerning malaria and their age, gender, education, and household monthly income were reported. Conclusions Malaria is still highly prevalent among rural Hausa communities in Nigeria. Despite high levels of knowledge and attitudes in the study area, significant gaps persist in appropriate preventive practices, particularly the use of ITNs. Innovative and Integrated control measures to reduce the burden of malaria should be identified and implemented in these communities. Community mobilization and health education regarding the importance of using ITNs to prevent malaria and save lives should be considered.